Stature and relative deprivation: Fatherless children in early industrial Britain. - Horrell, S; Humphries, J; Voth, H (Cambridge University Press, 1998)
Economic historians and development economists have exploited links between nutrition, health status and physical stature to argue that evidence about height can be used to supplement conventional economic indices of well-being. Evidence on stature may be available for time periods when conventional economic indices are not. It may also exist for sections of populations for which only aggregate income data is available, and so expose variations in living standards within populations: indeed this may be its most important contribution. Moreover height is an aggregate function of many aspects of well-being, including real income, work intensity and the disease environment. Unlike real income data it can reflect net environmental factors such as arduous employment at an early age that is not fully offset by inputs of food and health care. This article exploits these potentially useful attributes of the anthropometric approach to explore a neglected aspect of inequality in early industrial Britain and to try to capture evidence of the net effect of relative deprivation through cross-sectional analyses of heights. Children in families headed by women comprise the subsample on which we focus. Considerable qualitative and some quantitative evidence exists to suggest that children in such families were relatively deprived. Female-headed households were impoverished by the relatively low earning power of women, which was only partially offset by poor relief. But oppressive poverty was not alone in making these children's lives hard. Evidence suggests that they comprised a disproportionate share of child workers in the mines and manufactories of early industrial Britain. They were put to work early and at jobs which involved long hours and although their efforts augmented family incomes, given the poverty within which such families remained it is unlikely that the children's claim on resources was sufficiently boosted to offset the energy required by their employment.